2020
DOI: 10.1177/0091217420913001
|View full text |Cite
|
Sign up to set email alerts
|

Back pain and depressive symptoms: A systematic review and meta-analysis

Abstract: Background Low back pain is a common disorder that has many consequences. This study is an attempt to meta-analyze the risk of depression symptoms in back pain. Method Four databases were selected for review, and this search was conducted using key words. Eleven eligible articles were selected for review and meta-analysis was conducted. Subgroup analyses were continued with study design and the method of measuring depression. Also, the heterogeneity and publication bias were examined. Results Eleven cohort and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…Regarding sociodemographic factors associated with depressive symptoms among physicians, our study showed that the physicians who reported work-related illness were twice as likely to have depressive symptoms. Other studies found that work-related illnesses, such as workplace accidents or back pain, 60 increased patients' risk of developing depressive symptoms. In contrast, age, gender and monthly income did not show significant results.…”
Section: Explanation Of Results and Contrasting Within The Literaturementioning
confidence: 99%
“…Regarding sociodemographic factors associated with depressive symptoms among physicians, our study showed that the physicians who reported work-related illness were twice as likely to have depressive symptoms. Other studies found that work-related illnesses, such as workplace accidents or back pain, 60 increased patients' risk of developing depressive symptoms. In contrast, age, gender and monthly income did not show significant results.…”
Section: Explanation Of Results and Contrasting Within The Literaturementioning
confidence: 99%
“…Proinflammatory cytokines (IL-1β, IL-6 and TNF-α) may be screening biomarkers in the prediction of treatment response in patients with depression [56]. In addition, the relationship between back pain and depressive symptoms has also been reported by [59]. Overall, the Intervention seems to have a psychological effect by decreasing the symptoms of psychological distress and this could have been a cause of the decrease in IL-1β in the experimental group.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding sociodemographic factors associated with depressive symptoms among physicians, our study showed that the physicians who reported work-related illness were twice at risk of presenting with depressive symptoms. Other studies found that work-related illnesses, such as workplace accidents or back pain 41 , increased the patient's risk of developing depressive symptoms. Contrarily, age, gender, and monthly income did not show signi cant results.…”
Section: Relationship and Comparisons Between Variablesmentioning
confidence: 99%